Pilot study of sphenopalatine injection of onabotulinumtoxinA for the treatment of intractable chronic cluster headache. (May 2016) - Bratbak, Daniel Fossum; Nordgård, Ståle; Stovner, Lars Jacob; Linde, Mattias; Folvik, Mari; Bugten, Vegard; Tronvik, Erling
Objective: The main object of this pilot study was to investigate the safety of administering onabotulinumtoxinA (BTA) towards the sphenopalatine ganglion (SPG) in intractable chronic cluster headache. Efficacy data were also collected to provide indication on whether future placebo-controlled studies should be performed. Method: In a prospective, open-label, uncontrolled study, we performed a single injection of 25 IU ( n  = 5) or 50 IU BTA ( n  = 5) towards the SPG in 10 patients with intractable chronic cluster headache with a follow-up of 24 weeks. The primary outcome was adverse events (AEs) and the main efficacy outcome was attack frequency in weeks 3 and 4 post-treatment. Results: A total of 11 AEs were registered. There was one severe adverse event (SAE): posterior epistaxis. The number of cluster headache attacks (main efficacy outcome) was statistically significantly reduced in the intention-to-treat analysis from 18 ± 12 per week in baseline to 11 ± 14 ( p  = 0.038) in weeks 3 and 4, and five out of 10 patients had at least 50% reduction of attack frequency compared to baseline. The cluster attack frequency was significantly reduced for five out of six months post-treatment. Conclusion: Randomised, placebo-controlled studies are warranted to establish the potential of this possible novel treatment of cluster headache.